Dating the business cycle: Evidence from Mongolia - Davaajargal Luvsannyam; Khuslen Batmunkh; Khulan Buyankhishig (Central Bank Review (CBR), 2019)
Business cycle is an important indicator for making policy and management decisions. This paper compares the business cycle estimates for Mongolia based on a graphical and parametric methods. We find that Bry Boschan Quarterly (BBQ) algorithm accurately dates the business cycle which is consistent with the economic expectations. When we indicate the result of Bry Boschan Quarterly algorithm as the benchmark for the business cycle, trend filter provides a more precise estimate of the output gap for Mongolia.
Keywords: C18; E17; E32; 330; Business cycle; BBQ; I1 trend filter; HP filter; Expansion; Contraction; Hamilton filter; BN filter